Kultureel Jaarboek 84. (Gent : Provinciebestuur Oost-Vlaanderen, 1984)
Bockstaele, Herman ; de Cauter, Wim ; De Block, Luc ; Lonneville, Paule ; Peeters, Bert ; De Smedt, Albert ; Vandermoere, Henri ; Vandenberg, Philippe ; Castelein, Ingrid ; Burssens, Jan ; Landuyt, Octave ; Raveel, Roger ; Calmeyn, Jan ; Maet, Marc ; Verspeeten, Armand ; Dionyse, Carmen ; Heirbaut, Gisleen ; D'Havé, Camille
Nederlands
boek